Higher-order Mond-Weir converse duality in multiobjective programming involving cones - Yang, Xinmin; Yang, Jin; Yip, Tsz Leung; Teo, Kok Lay (Zhongguo Kexue Zazhishe, 2013)
In this work, we established a converse duality theorem for higher-order Mond-Weir type multiobjective programming involving cones. This fills some gap in recently work of Kim et al. [Kim D S, Kang H S, Lee Y J, et al. Higher order duality in multiobjective programming with cone constraints. Optimization, 2010, 59: 29–43].